TIFA Signaling in Gastric Epithelial Cells Initiates the cag Type 4 Secretion System-Dependent Innate Immune Response to Helicobacter pylori Infection - Alevtina Gall (American Society for Microbiology, 2017)
ABSTRACT Helicobacter pylori is a bacterial pathogen that colonizes the human stomach, causing inflammation which, in some cases, leads to gastric ulcers and cancer. The clinical outcome of infection depends on a complex interplay of bacterial, host genetic, and environmental factors. Although H. pylori is recognized by both the innate and adaptive immune systems, this rarely results in bacterial clearance. Gastric epithelial cells are the first line of defense against H. pylori and alert the immune system to bacterial presence. Cytosolic delivery of proinflammatory bacterial factors through the cag type 4 secretion system (cag-T4SS) has long been appreciated as the major mechanism by which gastric epithelial cells detect H. pylori. Classically attributed to the peptidoglycan sensor NOD1, recent work has highlighted the role of NOD1-independent pathways in detecting H. pylori; however, the bacterial and host factors involved have remained unknown. Here, we show that bacterially derived heptose-1,7-bisphosphate (HBP), a metabolic precursor in lipopolysaccharide (LPS) biosynthesis, is delivered to the host cytosol through the cag-T4SS, where it activates the host tumor necrosis factor receptor-associated factor (TRAF)-interacting protein with forkhead-associated domain (TIFA)-dependent cytosolic surveillance pathway. This response, which is independent of NOD1, drives robust NF-κB-dependent inflammation within hours of infection and precedes NOD1 activation. We also found that the CagA toxin contributes to the NF-κB-driven response subsequent to TIFA and NOD1 activation. Taken together, our results indicate that the sequential activation of TIFA, NOD1, and CagA delivery drives the initial inflammatory response in gastric epithelial cells, orchestrating the subsequent recruitment of immune cells and leading to chronic gastritis. IMPORTANCE H. pylori is a globally prevalent cause of gastric and duodenal ulcers and cancer. H. pylori antibiotic resistance is rapidly increasing, and a vaccine remains elusive. The earliest immune response to H. pylori is initiated by gastric epithelial cells and sets the stage for the subsequent immunopathogenesis. This study revealed that host TIFA and H. pylori-derived HBP are critical effectors of innate immune signaling that account for much of the inflammatory response to H. pylori in gastric epithelial cells. HBP is delivered to the host cell via the cag-T4SS at a time point that precedes activation of the previously described NOD1 and CagA inflammatory pathways. Manipulation of the TIFA-driven immune response in the host and/or targeting of ADP-heptose biosynthesis enzymes in H. pylori may therefore provide novel strategies that may be therapeutically harnessed to achieve bacterial clearance.